Feasibility study of the sheffield profile for assessment and referral for care. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Ahmed, Nisar; Hughes, Philippa; Winslow, Michelle; Bath, Peter; Collins, Karen; Noble, Bill
Abstract : Background: Sheffield profile for assessment and referral for care (SPARC) is a multidimensional holistic screening tool which provides a profile of needs (ie, physical, psychological, social, spiritual) to identify patients who may benefit from additional supportive or palliative care, regardless of diagnosis or stage of disease. Aim(s): A feasibility study (randomised controlled trial) is being undertaken to establish whether using SPARC improves care (impact on quality of life, interventions, consultations and referrals within supportive and palliative care), and to compare experience between patient groups. Method(s): The study is carried out within inpatients, out-patients, day care and in community settings, and is developed, piloted, evaluated, reported and implemented in accordance with the Medical Research Council framework for developing and evaluating complex interventions. Patients are randomised to receive SPARC at baseline or after a period of 2 weeks (waiting list control). Care continues as normal; SPARC responses are communicated to the care team to ensure identified needs are addressed. Participants are asked to complete three short research questionnaires as part of the study, repeated after 2, 4 and 6 weeks. A subgroup of participants were invited to participate in interviews. Results: In the first 6 months of data collection, 318 patients were invited to take part, 100 patients have consented (31.4% response rate). The number of completed questionnaires returned at the following time points are as follows; baseline: n=82, 2 weeks: n=65; 4 weeks: n=51; and 6 weeks: n=37. Sixteen patients have been interviewed. Interim results and methodological issues will be presented at the conference. Conclusion(s): Data generated from this feasibility study will guide the development of a further, larger definitive multi-centre study to define the clinical utility of SPARC.